Factors Influencing Consumers’ Co-Creation Value and Purchase Intention of the Virtual Brand Community in Guangdong, China - Li, Hongwei (Scholar: Human Sciences, 2024)
Purpose: This study aims to investigate the key influencing factors of co-creation value and purchase intention of internet users in virtual brand communities in Guangdong Province, China. The conceptual framework proposes the causal relationships among self-service, co-reflection, user engagement, trust, co-creation value, and customer purchase intention. Research Design, data, and methods: Using a quantitative approach (N = 500), the researchers administered questionnaires to five representative virtual brand communities in Guangdong, China, including Xiaomi Fans Club and Perfect Diary Brand WeChat Group, Watsons official user community, Starbucks WeChat User Community, NetEase Cloud Music Virtual Community. The sampling procedures includes judgmental, stratified random, and convenience sampling, collecting data and distributing online and offline surveys. Structural Equation Model (SEM) and confirmatory factor analysis (CFA) were used to analyze the data, including model fit, reliability and validity. Result: The results show that self-service, co-reflection, user engagement, and trust significantly influence co-creation value. Furthermore, trust and co-creation value significantly influence customer purchase intention. Conclusion: The findings can help the virtual brand community develop a new way to disseminate and promote product information through social networking sites. This research also helps to build a positive perception of products and services, as a positive orientation will thus influence purchasing decisions.